Aneurysm Wall Enhancement Is Associated With Decreased Intrasaccular IL-10 and Morphological Features of Instability. Issue 4 (9th July 2021) - Swiatek, Vanessa M; Neyazi, Belal; Roa, Jorge A; Zanaty, Mario; Samaniego, Edgar A; Ishii, Daizo; Lu, Yongjun; Sandalcioglu, I Erol; Saalfeld, Sylvia; Berg, Philipp; Hasan, David M
Abstract: BACKGROUND: High-resolution vessel wall imaging plays an increasingly important role in assessing the risk of aneurysm rupture. OBJECTIVE: To introduce an approach toward the validation of the wall enhancement as a direct surrogate parameter for aneurysm stability. METHODS: A total of 19 patients harboring 22 incidental intracranial aneurysms were enrolled in this study. The aneurysms were dichotomized according to their aneurysm-to-pituitary stalk contrast ratio using a cutoff value of 0.5 (nonenhancing < 0.5; enhancing ≥ 0.5). We evaluated the association of aneurysm wall enhancement with morphological characteristics, hemodynamic features, and inflammatory chemokines directly measured inside the aneurysm. RESULTS: Differences in plasma concentration of chemokines and inflammatory molecules, morphological, and hemodynamic parameters were analyzed using the Welch test or Mann-Whitney U test. The concentration ΔIL-10 in the lumen of intracranial aneurysms with low wall enhancement was significantly increased compared to aneurysms with strong aneurysm wall enhancement ( P = .014). The analysis of morphological and hemodynamic parameters showed significantly increased values for aneurysm volume ( P = .03), aneurysm area ( P = .044), maximal diameter ( P = .049), and nonsphericity index ( P = .021) for intracranial aneurysms with strong aneurysm wall enhancement. None of the hemodynamic parameters reached statistical significance; however, the total viscous shear force computed over the region of low wall shear stress showed a strong tendency toward significance ( P = .053). CONCLUSION: Aneurysmal wall enhancement shows strong associations with decreased intrasaccular IL-10 and established morphological indicators of aneurysm instability.